2017
DOI: 10.2147/ceor.s145813
|View full text |Cite
|
Sign up to set email alerts
|

Setting priorities in the health care sector – the case of oral anticoagulants in nonvalvular atrial fibrillation in Denmark

Abstract: AimResources devoted to health care are limited, therefore setting priorities is required. It differs between countries whether decision-making concerning health care technologies focus on broad economic perspectives or whether focus is narrow on single budgets (“silo mentality”). The cost perspective as one part of the full health economic analysis is important for decision-making. With the case of oral anticoagulants in patients with nonvalvular atrial fibrillation (NVAF), the aim is to discuss the implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…One meeting abstract was identified from International Society of Pharmacoeconomic and Outcomes Research and one study from manual searches met the inclusion/exclusion criteria, resulting in 186 total publications (159 unique studies) with direct costs, resource use and/or indirect costs. Among the 186 publications, 15 reported indirect costs (14 unique studies and one related publication reporting on the same study population) [34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Study attrition through the abstract and full-text screening levels are detailed in the PRISMA diagram in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…One meeting abstract was identified from International Society of Pharmacoeconomic and Outcomes Research and one study from manual searches met the inclusion/exclusion criteria, resulting in 186 total publications (159 unique studies) with direct costs, resource use and/or indirect costs. Among the 186 publications, 15 reported indirect costs (14 unique studies and one related publication reporting on the same study population) [34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Study attrition through the abstract and full-text screening levels are detailed in the PRISMA diagram in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…The cost analysis was based on data from randomised studies on clinical endpoints with evolocumab and alirocumab 10 16. Clinical endpoints considered were death, MI, stroke, major adverse CV events (MACEs, death from CV causes, non-fatal MI, unstable angina requiring hospitalisation, an ischaemia-driven coronary revascularisation procedure or non-fatal ischaemic stroke), or the composite endpoint death, MI, stroke for the ODYSSEY OUTCOMES study, MI, stroke, MACE (CV death, MI, stroke, hospitalisation for unstable angina, coronary revascularisation), the composite endpoint CV death, MI, stroke for the FOURIER study.…”
Section: Methodsmentioning
confidence: 99%
“…However, such ‘rigorous’ approach to cost-effectiveness analysis does not always encompass the whole spectrum of cost burden of drugs and therapies. Studies such that from Poulsen et al show that, with a pharmacoeconomic analysis considering just the cost of a new drug, it is often impossible to appreciate the whole possible positive impact following the introduction of a new treatment; that is the case of direct anticoagulants in the prevention of thromboembolic complications of atrial fibrillation 16. When, instead, also individual, municipality and social costs are duly weighted, apparent increased costs may turn into considerable savings.…”
Section: Introductionmentioning
confidence: 99%
“…11 Another study in Denmark estimated the mean annual medical cost (including medication cost, monitoring and follow-up visit cost) of warfarin, dabigatran, rivaroxaban and apixaban to be USD933, USD909, USD921 and USD1047, respectively. 12 Nevertheless, the healthcare system in Malaysia is different to that of Australia and the US the because the Malaysian government finances the public health services through the Consolidated Revenue Fund while private sector patients essentially meet their own medical costs. 13 The increasing use of NOACs following their introduction to The Ministry of Health Medicines Formulary in Malaysia in 2009, led to substantial increases in expenditure in government funded hospitals, due to the high drug acquisition costs of NOACs.…”
Section: Introductionmentioning
confidence: 99%
“…A study in the United States showed that despite higher medication cost, overall annual healthcare cost for dabigatran therapy was USD1940 significantly lower than warfarin therapy 11 . Another study in Denmark estimated the mean annual medical cost (including medication cost, monitoring and follow‐up visit cost) of warfarin, dabigatran, rivaroxaban and apixaban to be USD933, USD909, USD921 and USD1047, respectively 12 . Nevertheless, the healthcare system in Malaysia is different to that of Australia and the US the because the Malaysian government finances the public health services through the Consolidated Revenue Fund while private sector patients essentially meet their own medical costs 13 …”
Section: Introductionmentioning
confidence: 99%